2004
DOI: 10.1081/ada-200032290
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Long‐Term Residential Substance Abuse Treatment for Women: Findings from Three National Studies

Abstract: The effectiveness of residential substance abuse treatment for women was examined using data from the Center for Substance Abuse Treatment's Residential Women and Children/Pregnant and Postpartum Women (RWC/PPW) Cross-Site Study and two other recent national studies. Treatment success was defined as posttreatment abstinence from further drug or alcohol use, measured through in-person follow-up interviews conducted 6-12 months after each client's discharge. Despite differences in treatment programs, client prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
67
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 9 publications
10
67
0
2
Order By: Relevance
“…Todavía hoy, existe controversia sobre cómo valorar el éxito terapéu-tico en una CT. La mayoría de los autores están de acuerdo en considerar el tiempo de estancia como un indicador válido de resultados, siendo tres meses el tiempo medio estimulado para que el paciente pueda presentar una mejoría clínicamente relevante (Condelli y Hubbard, 1994;Greenfield, Burgdorf, Chen, Porowsk, Roberts y Herrell, 2004;Vergara-Moragues, 2010). Otros estudios longitudinales indican que algunas variables relacionadas con el paciente tienen un valor predictivo limitado sobre los resultados de tratamiento, al explicar un porcentaje de la varianza relativamente bajo de éstos (Condelli, 1994;Secades y Fernández, 2000).…”
unclassified
“…Todavía hoy, existe controversia sobre cómo valorar el éxito terapéu-tico en una CT. La mayoría de los autores están de acuerdo en considerar el tiempo de estancia como un indicador válido de resultados, siendo tres meses el tiempo medio estimulado para que el paciente pueda presentar una mejoría clínicamente relevante (Condelli y Hubbard, 1994;Greenfield, Burgdorf, Chen, Porowsk, Roberts y Herrell, 2004;Vergara-Moragues, 2010). Otros estudios longitudinales indican que algunas variables relacionadas con el paciente tienen un valor predictivo limitado sobre los resultados de tratamiento, al explicar un porcentaje de la varianza relativamente bajo de éstos (Condelli, 1994;Secades y Fernández, 2000).…”
unclassified
“…The results showed that the abstinence rate was 76%-78% for three months and achieved their treatment goals in three to five months abstinence. The abstinence rate for patients who did not complete the treatment was 51%-52% (17).…”
Section: Methodsmentioning
confidence: 99%
“…Greenfield, Burgdorf, Chen, Porowski, Roberts, Herrell (17) in 2004 examined the abstinence rate of women involved in residential substance abuse treatment. The results showed that the abstinence rate was 76%-78% for three months and achieved their treatment goals in three to five months abstinence.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7][8] Several observational studies have found longer stays in residential programs to improve outcomes in women. 9,10 In more recent randomized trials, longer stays have been associated with either no benefits or only beneficial effects on some of several outcomes. Witbrodt et al found that longer length of residential and day hospital addiction treatment up to 2 months, but not beyond, was associated with greater likelihood of abstinence at follow-up.…”
mentioning
confidence: 98%